Relationship between Emotional States and Coping Styles Among High Risk Students - Mohd Khairul Anuar Rahimi; Kamal Abdul Rahman; Farhana Sabri (Universiti Sains Islam Malaysia, 2024)
This study was conducted to examine the relationship between emotional states and coping styles among high risk students in five secondary schools at the Hilir Perak district. This study identified the coping styles among high risk students and examined the relationship between emotional states and coping styles among high risk students. This quantitative study was done by using a survey research design. A total of 140 students consisting of Form One to Six students were selected as respondents in the study. Depression Anxiety Stress Scale (DASS) was used to measure depression, anxiety and stress levels while the Soal Selidik Gaya Daya Tindak (SSGDT) was used to measure coping styles. Data were analysed by using descriptive and inferential statistics. Inferential analysis using Pearson r correlation statistical analysis were used for variables to be compared using interval measurement scales. Findings indicate the level of depression and stress for high risk student is at a normal level while the level of anxiety is in a mild level. Correlational analysis indicate that the level of anxiety and stress levels were correlated with their coping style.